Quo Vadis Pembaharuan Hukum Pertanahan Nasional - Fuad, Muhammad Busyrol (Lentera Hukum, 2017)
The rise of national agraria conflicts that occurred seem to have been in the point is quite worrisome. Because he has a slice of various forms of human rights dimensionless violations. Various discourses in the effort to resolve the conflict continue. The discourse on the creation of a special court of land seems to have begun to gain a lot of attention. The reason, he is present in the situation of national agraria conflict that never ends, besides the passage of this discourse is full of momentum, which coincides with the draft Land Law Bill which is now entered the political space of legislation in parliament. A special court of land will certainly be a topic of discussion is quite fierce considering the issue will reach the settlement areas of national agraria cases that include land tenure by the plantation company (onderneming), PT. Perkebunan Nasional (PTPN), to the control of land by the military. This paper would like to discuss that the establishment of a special land court in the draft national land law is a necessity in solving a just national agrarian conflict. Keyword: Agraria Conflict, Violations of Human Rights, Special Court of Land